Degradasi Budaya Betawi pada Atraksi Ondel-Ondel Jalanan - Derinta Entas; Ni Made Dwiyana Rasuma Putri; Heru Suheryadi; Mochammad Aliff (STIEPAR YAPARI Bandung, 2022)
The purpose of this study was to find factors that indicate the cause of betawi cultural degradation in ondel-ondel street attractions in the cities of Jakarta and South Tangerang. Qualitative and interpretive descriptive research methods with three key informants, namely Betawi community leaders, communities who are members of local cultural observers and Ondel-ondel parade/buskers. The result of this study is the shift of belief in ondel-ondel which raises pros and cons in the betawi ethnic community. This condition is believed to be a consequence of the social, economic and cultural changes of the Betawi ethnic community itself. Identification of factors that support this shift includes: (1) The struggle for the meaning of tradition and religion; (2) The struggle for economic significance; and (3) The struggle for the meaning of globalization. Of these three factors, economic factors are the main ones due to the demands for a better economic life. The tendencies mentioned are empirical facts that cannot be ignored for the phenomenon of betawi cultural degradation, especially in the ondel-ondel attractions of the streets.